Rancang Bangun Aplikasi Pembelajaran Aksara Jawa Berbasis Android - Hambali, Imam; Sunarto, M. J. Dewiyani; Sutanto, Teguh (Jurnal JSIKA, 2013)
Javanese script as one of Indonesian cultural heritage is increasingly abandoned. Elementary school students who are still learning and still having trouble considered less interest to learn java script. Many factors are influence, one of which is media literacy learning Java is less interesting. With the progress of time learning media can be presented on a mobile device. Android is a mobile operating system that can bring about change in the areas of learning. With a variety of features as well as the support provided, many learning applications that can be produced and development of Android. Therefore the author would like also to create an application-based learning android javanese script. Based on the resulting system and a series of trials that have been done, this system will be used to write the script and check the truth writing with the help of an Application Programming Interface (API) Gesture. Besides that, application can be used to introduce the characters, convert the latin letters to javanese script with the help of java script font hanacaraka. With a variety of features in it would be very helpful users are still difficult to learn javanese script.